Estudio de factibilidad para la exportación de café tostado a Ottawa-Ontario Canadá por parte de la asociación de mujeres cafeteras del occidente del Huila “las rosas coffee” del municipio de la Plata Huila (2023)
Colombia, and in particular the department of Huila, are one of the most important coffee producers in the world, in terms of quantity and superior quality of the product, despite the current post-pandemic crisis that has dramatically affected not only its own regional situation, but also that of all international markets. In response to this problematic situation, it is specified that this research has the general objective of carrying out a pre-feasibility study to investigate the possibilities of exporting roasted coffee, produced by the association of women coffee growers "Las Rosas Coffee", from the municipality of La Silver - Huila, bound for the city of Ottawa -Ontario, Canada.